Comparative Study of Schoology and OpenLearning E-Learning Platforms for Enhancing English Skills - Rakhmadi Aris; Haryanti Yanti (E3S Web of Conferences)
This study investigates the interactions between different teaching strategies and student Cumulative Academic Scores (CAS), particularly their effects on the English scores of students at the University of Muhammadiyah Surakarta. It aims to determine if significant differences exist in English Proficiency Exam (EPE) scores among students using conventional methods, the Schoology platform, and OpenLearning while controlling for CAS. The results indicate a statistically meaningful interaction between teaching strategies and CAS, suggesting that the instructional approach can influence English proficiency outcomes. Notably, students utilizing the Schoology platform achieved the highest average EPE score of 422.99, outperforming both traditional and OpenLearning clusters, underscoring the platform’s effectiveness in enhancing student performance. The analysis also highlights significant differences in EPE scores across the three learning clusters and a positive correlation between CAS and EPE scores, reinforcing the link between academic achievement and assessment performance. Based on these results, the study recommends that the university implement an online learning policy focused on the Schoology framework while reconsidering other mandatory implementations of OpenLearning to provide students a more effective learning experience.